2007
DOI: 10.1073/pnas.0601437104
|View full text |Cite
|
Sign up to set email alerts
|

Protective role of autophagy against Vibrio cholerae cytolysin, a pore-forming toxin from V. cholerae

Abstract: Autophagy is the unique, regulated mechanism for the degradation of organelles. This intracellular process acts as a prosurvival pathway during cell starvation or stress and is also involved in cellular response against specific bacterial infections. Vibrio cholerae is a noninvasive intestinal pathogen that has been studied extensively as the causative agent of the human disease cholera. V. cholerae illness is produced primarily through the expression of a potent toxin (cholera toxin) within the human intestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
151
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 161 publications
(160 citation statements)
references
References 49 publications
7
151
2
Order By: Relevance
“…Interestingly, recent studies indicate that the bacterial pore-forming toxins listeriolysin O and Vibrio cholerae's cytolysin trigger autophagy. 41,42 By analogy, the membrane channel activity of VacA within vacuoles may be sufficient to induce autophagy perhaps by inducing vacuolar damage as has recently been described for Salmonella. 43 Autophagy can also be triggered by the exposure of mammalian cells to stress conditions, such as nutrient deprivation.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, recent studies indicate that the bacterial pore-forming toxins listeriolysin O and Vibrio cholerae's cytolysin trigger autophagy. 41,42 By analogy, the membrane channel activity of VacA within vacuoles may be sufficient to induce autophagy perhaps by inducing vacuolar damage as has recently been described for Salmonella. 43 Autophagy can also be triggered by the exposure of mammalian cells to stress conditions, such as nutrient deprivation.…”
Section: Discussionmentioning
confidence: 99%
“…A host cell can use autophagy to prevent the cytoplasmic replication or invasion of intracellular pathogens by engulfing the pathogens in autophagic vesicles and targeting them to lysosomes (28). In addition, recent work has shown that autophagy may provide defense against a secreted toxin from the noninvasive pathogen Vibrio cholerae (29). Alternatively, pathogens have evolved ways to usurp this pathway for their own benefit: for example, the intracellular pathogen Coxiella burnettii creates a replicative niche within autophagosomes where it can multiply and survive (30).…”
Section: Discussionmentioning
confidence: 99%
“…In this context, it has been reported that tumor promoter agents (e.g., phorbol esters), growth factors, and DNA damage are involved in the regulation of KLF6 protein level correlating with the proliferation control and cell death (22,26,36). Moreover, recent results indicate that the endogenous KLF6 protein level is responsive to the intoxication triggered by the Vibrio cholerae cytolysin (Saka H. A., Andreoli V., and Bocco J. L., unpublished), which is able to trigger apoptosis and autophagy in human intestinal epithelial cells (50)(51)(52).…”
Section: Klf6mentioning
confidence: 99%